Human Resource Development Strategies and Their Impact: Insights from Pondok Pesantren Darul Muhajirin - Ashuri, Mizan (JURNAL PENELITIAN KEISLAMAN, 2024)
This study focuses on the enhancement of human resources by the leadership of Darul Muhajirin Islamic Boarding School in Praya. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The analysis included data collection, condensation, display, and conclusion drawing. Findings reveal that the leadership strategy includes formulating a vision, planning, directing, decision-making, problem-solving, and evaluation, with programs such as training, halaqah, and improving teacher performance. Implementation involves planning, program design, policy management, and stakeholder involvement. The impacts on the quality of the pesantren include improvements in teaching quality and a stronger pesantren identity, but also financial burdens and resistance to development programs.